Expanding the Scope of Practice for Pharmacists in Ontario - Glen Edward Randall; Neil G. Barr; Patricia A. Wakefield; Mark G. Embrett (McMaster University Library Press, 2015)
On 15 December 2009 the Regulated Health Professions Statute Law Amendment Act, 2009 (Bill 179) received Royal Assent in Ontario. The resulting legislative amendments were intended to strengthen government oversight of the health regulatory colleges, promote interprofessional collaboration, and make better use of health professionals' existing skills and training by enhancing the scope of practice for several health professions in order to improve health system efficiency. Among the most notable scope of practice enhancements were those given to pharmacists, who would be permitted to: modify and renew existing prescriptions, prescribe a limited range of drugs independent of a physician, and administer medications such as vaccinations via injection or inhalation. The reform was driven in large part by the government's concerns related to the rising cost of health care, the public's desire for greater access to services, and demonstrated successes of similar reforms in other jurisdictions. While the Ontario reform has had some clear success, such as expanding the public's access to influenza vaccinations, to date, the evidence of achieving other goals remains weak. In particular, there is no clear evidence of improved health system efficiency and associated cost effectiveness. Moreover, it is possible that Ontario's umbrella regulatory model may be making interprofessional collaboration more, rather than less, difficult to realize.